ANALYSIS OF STUDENTS’ DIFFICULTIES IN TRANSLATING ARGUMENTATIVE TEXTS FROM ENGLISH TO INDONESIAN AT UIN MATARAM: A STUDY OF LINGUISTIC AND NON-LINGUISTIC FACTORS - Putri Maela Salsabila (Journal of English Education and Literature, 2025)
This study aims to analyze the difficulties experienced by students in translating argumentative texts from English to Indonesian, especially based on linguistic and non-linguistic factors. The research subjects are final semester students of English Education Study Program at UIN Mataram who have taken translation courses. The method used was descriptive qualitative with data collection techniques in the form of translation tests and semi-structured interviews. The results showed that linguistically, students had difficulties in understanding technical vocabulary, idiomatics, and complex sentence structures in argumentative texts. Meanwhile, non-linguistically, the obstacles include limited understanding of cultural context, lack of topic background knowledge, and low self-confidence in dealing with foreign texts. This study concludes that difficulties in translating argumentative texts are multidimensional and demand a holistic learning approach, including strengthening translation strategies, improving cultural understanding, and training critical thinking skills. The findings are expected to serve as a reference in the development of more effective translation curriculum and teaching methods in higher education.